1997
DOI: 10.1089/neu.1997.14.897
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tetrahydroaminoacridine, a Cholinesterase Inhibitor, on Cognitive Performance Following Experimental Brain Injury

Abstract: An emerging literature exists in support of deficits in cholinergic neurotransmission days to weeks following experimental traumatic brain injury (TBI). In addition, novel cholinomimetic therapeutics have been demonstrated to improve cognitive outcome following TBI in rats. We examined the effects of repeated postinjury administration of a cholinesterase inhibitor, tetrahydroaminoacridine (THA), on cognitive performance following experimental TBI. Rats were either injured at a moderate level of central fluid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Pike et al [37] reported that tetrahydroaminoacridine (tacrine) failed to improve cognitive performance in traumatically brain-injured rats, and actually worsened performance on the Morris water maze task. Although this finding may initially present a challenge to the cholinergic hypothesis and limit enthusiasm for the potential benefits of cholinesterase inhibition in this population, it is important to observe that tacrine also antagonizes Nmethyl-D-aspartate receptors [38].…”
Section: Cholinergic Dysfunction After Traumatic Brain Injury: Animalmentioning
confidence: 99%
“…Pike et al [37] reported that tetrahydroaminoacridine (tacrine) failed to improve cognitive performance in traumatically brain-injured rats, and actually worsened performance on the Morris water maze task. Although this finding may initially present a challenge to the cholinergic hypothesis and limit enthusiasm for the potential benefits of cholinesterase inhibition in this population, it is important to observe that tacrine also antagonizes Nmethyl-D-aspartate receptors [38].…”
Section: Cholinergic Dysfunction After Traumatic Brain Injury: Animalmentioning
confidence: 99%
“…None of the doses were effective in attenuating cognitive decline after injury, and the highest dose appeared to worsen cognitive outcome. Pike and colleagues [22] offer several possible explanations for the negative behavioural effects reported in this study. Previous research has suggested that repeated cholinesterase inhibition may reduce ACh synthesis because extracellular ACh is forced to compete for choline uptake sites [80].…”
Section: Cholinergic Systemmentioning
confidence: 84%
“…Although this score is an approximation, a basic comparison allows one to note the percentage of cognitive enhancement. THA [22] and haloperidol [50] were not included in the figure because each resulted in impaired cognitive performance. Olanzapine [50] and fluoxetine [23] were also not included because each resulted in a neutral effect on cognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations